Implikatur Percakapan Antartokoh dalam Film Cek Toko Sebelah Karya Ernest Prakasa - Nurul Islamiyah (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Implicature of the conversation can occur depending on the use of language and speech context. The use of this language is related to the functions of the language (language functions), while the context is part outside the language that builds speech or discourse. This study aims to (1) describe the types of implicature contained in the conversation between the characters of the Check Shop Side movie, and (2) describe the function of the conversational implicature in the film Check the Store Next Door. The subjects in this study were conversations that contained conversational implicature in the film Check the Store Next Door directed by Ernest Prakasa with a duration of 01 hours 44 minutes 13 seconds. The object of his research is the conversational implicature contained in the Check the Store Next Door film. This type of research is a qualitative descriptive study. The data collection technique was carried out by researchers by referring to and taking notes. The researcher uses the implicature theory as the main reference for conducting research analysis. The results of the study are as follows. First, there are three types of implicature found, namely general conversation implicature and special conversation implicature. From the appearance side, the most dominant form of speech is the general conversation implicator which amounts to 15 and the specific conversation implicator counts 9. Second, the implicature functions found in this study are 21, namely the representative function 9, directive function 7, and expressive function 5. From this research is expected to be able to find meaning in a film that will be useful with references in life.